Adat Turun Tanah Bagi Suku Jawa Di Kota Palangka Raya Ditinjau Dari Prespektif Islam - Miftahul Miftahul (LP2M IAIN Palangka Raya, 2015)
This study took place in the cit y of. This research is a custom object off the ground for Javanese conducted by the public in Palangkaraya. The approach used is descripive qualitative data collection techniques such as interviews, observation, and documentation. Validation data using triangulation techniques and to analyze the data through several stages, namely: data collection (Data Collettion), data reduction (Data Reduction), data presebtation (Data Display), and then the new conclusion (Conclusions Data) by looking back at the data that has been collected. The results showed that the customary land down since time immemorial have been made of their ancestors and continue to this day, they are considered custom picture off the ground known as the child’s talents or interests that relate man to God Almighty to always tangible safety, protection, peace, and prosperity in life. Furthermore, the results of the analysis of the study stated that the customs off the ground in the city of Palangkaraya nothing that violates the Islamic law. So if there are irregularities in the implementation of the Islamic law, then the y should not be implemented custom not to be involved in the case shirk.